Assessment of Soil Infiltration Capability in Balikpapan City - Juwita, Ratna; Santoso, Irwan Bagyo (IPTEK Journal of Proceedings Series, 2019)
This study aims to determine the ability of soil infiltration in the city of Balikpapan. The analysis begins by testing the infiltration rate in the field using Double-ring Infiltrometer. Measurements were made in 15 research locations spread across Balikpapan City. Location determination is seen from changes in land and soil type functions in Balikpapan City based on regional administrative maps, land type maps, land use maps and Balikpapan City RTRW. Furthermore, the results of field measurements are processed using the Horton model. The Horton model is one of the well-known infiltration models in hydrology. From the results of research at 15 locations, it was concluded that Balikpapan City had an infiltration rate between the range of 12 mm / hour to 240 mm / hour. Based on U.S. Soil Conservation, the infiltration rate classification in Balikpapan City is divided into four infiltration rate classes, namely fast, rather fast, medium and rather slow. Areas that have the potential to be rainwater catchment areas are seen from areas that have as many as 10 locations from 15 locations, namely Prapatan, Telaga Sari. Sources Rejo, Manggar Baru, Damai Baru, Kariangau, Gunung Sari Ulu, Margo Mulyo, Graha Indah and Mount Bahagia. So the area that has the potential as a catchment area is around 60% of all research locations. From the analysis results obtained by the type of rainwater management facilities in the form of PAHs and / or retention facilities for housing, education, trade and services with rapid, rather rapid infiltration, while PAHs and / or retention facilities and / or detention facilities for infiltration rates. a little slow